Profile of Creative Thinking In Science Learning In Junior High School For The Different Gender - Nurul Qomariah; Suratno Suratno; Yushardi Yushardi (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2017)
Creative thinking including higher order thinking. Creative thinking is very important in the learning of science. Often there is a difference in creative thinking in both male and female. The purpose of this research is to determine the profile of creative thinking skills in science learning in junior high school to the different gender. This research is descriptive methods. Creative thinking skill is measured by creative thinking rubric. The Data were analysed using descriptive quantitative using Microsoft Excel. The result of research has a variate creative thinking skills in science learning process in male and female.